(untitled) (Wanastra: Jurnal Bahasa dan Sastra, 2025)
Integrating short movies seems to be interesting and exciting in English English-speaking classroom. This research was aimed at investigating the effect of short movies with a retelling technique on English-speaking achievement. Six research questions were tailored to predict. A quasi-experimental research design, which was merely concerned with the comparison group research design, was used in this research. Purposive sampling was employed in which consisted of twenty-eight participants, as the population, with equal size comprising fourteen participants, respectively. An English-speaking assessment as the instrumentation was performed with an analytical scoring rubric used to collect the data of EFL learners’ speaking performance. The research process was successfully done to answer the six predicted research questions. In conclusion, using a short movie with a retelling technique gave significant improvement on EFL learners’ English speaking analytically and holistically, as the p-value was lower than the conventional level of significance. Besides, the percentage distribution to respective aspects of speaking was fluency (88.7%), vocabulary (7.5%), pronunciation (2.1%), comprehension (.7%), and grammar (.6%). Some thorough and systematic conclusions and pedagogical implications were tactfully written out.